Behavioural And Biological Risk Factors of Non-Communicable Diseases Among the Selected Tribal People of Pune District - Jamdade, Vinita; Kumar Ray, Suresh; Bidari, Ramesh (Journal of Neonatal Surgery, 2025)
Introduction: Non-communicable diseases (NCDs) are a growing concern globally, contributing to millions of deaths, especially in low- and middle-income countries. In India, NCDs account for a significant proportion of deaths, and rural tribal populations are increasingly vulnerable to these diseases due to changing lifestyles. This study focuses on assessing behavioural and biological risk factors for NCDs among tribal adults in Pune District. Aims of the Study: To evaluate the prevalence of behavioural and biological risk factors for NCDs in the tribal population of Pune District, Methodology: A quantitative, descriptive research design was employed, with 100 tribal adults selected using a non-probability convenient sampling method. Data were collected through demographic surveys, anthropometric measurements, and health screenings, including blood pressure, blood glucose levels, and urine analysis. Results: The majority of participants were males (58%), aged 35-44 years (28%), with a significant prevalence of tobacco (58%) and alcohol use (52%). Elevated blood pressure (65%) and abnormal biological parameters, such as blood glucose and urine protein, were observed, indicating potential NCD risks. Conclusion: The study highlights the high prevalence of NCD risk factors in the tribal population of Pune District. Despite the awareness of these risks, the management and control of blood pressure and blood glucose were suboptimal, emphasizing the need for improved healthcare interventions in this population.